Morphological diversity and genetic differentiation of PO cattle in smallholder farmers - ., Hartati; ., Sumadi; ., Subandriyo; Hartatik, Tety (Indonesian Journal of Animal and Veterinary Sciences, 2010)
PO cattle is one of  the local cattle with high genetic diversity. The aim of this research was to study genetic diversity of PO cattle in smallholder farmer  based on morfology and molecular markers. This research was conducted at breeding center in East Java and Central Java include Tuban, Lamongan and Blora regency, since June until December 2008.  PO bull used were of 18 months until 24 months of age and cow of 24 months until 36 months of age or at first calving as much as 30 head each location. The variables measured were body weight, body length, withers height, hip height, shoulder point width, chest girth, chest depth, canon bone circumference, head length and head width. Data were analyzed using descriptive statistic, average analysis between subpopulations, discriminant and canonical analysis and mahalanobis distance was done by SAS DISCRIM procedure. Whole blood were collected to get the data of polymorphism DNA microsatellite using technology of PCR and electrophoresis using 6 microsatellite loci. Variable measured were number and size of  alel, alel frequency, heterozygosity,genetic distance and fixation index (F-stat). Data were analyzed using analysis of Microsate Toolkit, GENEPOPV4, MSA (Microsatellite Analyser) and Mega 4. The result showed that Blora and Tuban subpopulation have genetic diversity which is relative lower  compared to that of Lamongan. The genetic distance which was close presented by Tuban and Blora subpopulation while Lamongan and Tuban subpopulation show far genetic distance. The result of canonical analyses showed  high correlation on shoulder point width, head width, body length, withers height and hip height variable so this five variable can be used as distinguishing variables among subpopulation. The result of molecular genetics analysis using microsatellite showed that highest frequency of alel presented by HEL9 locus at Tuban population so this loci have the high polymorfism. The genetic differentiation among subpopulation showed by differentiation FST value among six loci  indicating the increasing of inbreeding in  the three subpopulations. Key words: Morphological Diversity, Genetic Differentiation, PO Cattle